Psychometric validation of a culturally adapted health belief model scale for breast cancer screening in Chinese women - Yang Liao; Suhaily Mohd Hairon; Najib Majdi Yaacob; Tengku Alina Tengku Ismail; Li Luo (PLoS ONE, 2025)
This study aimed to validate a culturally adapted Health Belief Model (HBM) questionnaire for assessing breast cancer screening beliefs among Chinese women and to evaluate its structural validity and measurement invariance. A cross-sectional survey was conducted with 314 women aged 18–70 in Guizhou Province, China, using multistage sampling. The original HBM questionnaire underwent cultural adaptation and expert content review. Exploratory and confirmatory factor analyses were conducted to examine the factor structure, and measurement invariance was tested across residential settings and age groups. A seven-factor solution was identified, encompassing all six core HBM constructs, with self-efficacy splitting into two empirically distinct dimensions. The final 41-item model demonstrated strong model fit (CFI = 0.914, TLI = 0.906, RMSEA = 0.059, SRMR = 0.060), high internal consistency (ω ≥ 0.88), and full invariance across subgroups. Convergent validity and inter-construct correlations aligned with theoretical expectations. In particular, strong positive associations were observed among self-efficacy, perceived benefits, and cues to action, while perceived barriers showed inverse relationships with perceived severity and risk perception. These findings offer empirical justification for both single-construct and multi-construct intervention strategies. The validated scale provides a psychometrically sound and culturally grounded tool for identifying psychological barriers to screening among Chinese women. It may guide the design of theory-informed public health interventions that address individual belief profiles and promote screening uptake.